Coupled Electromagnetic Circuits and Their Connection to Quantum Mechanical Resonance Interactions and Biorhythms and the Quantization of Resonators with Importance in other Fields of Physics and Applications - Ulmer, W.; Cornelissen, G. (Current Research Progress in Physical Science Vol. 6, 2024)
A biorhythm is any repetitive molecular, physiological, or behavioral event or process. The study of biorhythms is of both fundamental and practical importance. The existence of specific biorhythms and the role of geomagnetic and/or solar magnetic activities are well-established by appropriate correlations in chronobiology. From a physical viewpoint, there are two different accesses to biorhythms to set up connections to molecular processes: quantum mechanical perturbation theoretical methods and their resonance denominators to characterize specific interactions between constituents. These methods permit the treatment of molecular processes by circuits with characteristic resonances and “beat-frequencies”, which result from primarily fast physical processes. For example, the tunneling processes between DNA base pairs (H bonds), the ATP decomposition, and the irradiation of tumor cells are accounted for. The quantization of coupled resonators opens a further field with scientific importance, e.g., three coupled oscillators characterized by SU3-symmetry with applications in particle and nuclear physics due to the interaction with the Higgs field. The method can be extended to molecular processes and shows a connection between chronobiology and quantum theoretical entanglement.